HUBUNGAN ANTARA NILAI-NILAI KARAKTER DAN DUKUNGAN TEMAN SEBAYA DENGAN PENYESUAIAN AKADEMIK SISWA KELAS XI DI SMAN 3 PALANGKA RAYA - Widyasti, Evany (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2024)
One of the main obstacles faced by the world of education in Indonesia is the low academic adjustment where students are still difficult to adjust to academic changes from junior high school (SMP) to senior high school (SMA) level applied at school. Researchers found the phenomenon of academic adjustment that occurred at SMAN 3 Palangka Raya, especially students of class XI IPS from the results of interviews with the BK coordinator Mrs. Erna Sugiarti, S.Pd, namely students who violated the rules at school as many as 90 students or 49%, did not do homework assignments (homework) as many as 24 students or 13% and were disrespectful as many as 12 students or 6%. This study aims to determine the relationship between character values and peer support with academic adjustment of class XI students at SMAN 3 Palangka Raya. Population more than 100 people then taken 10% of the population. So the sample of this study was taken from 3 classes of 110 students, namely students of class XI IPS 1 totaling 37 people, class XI IPS 2 totaling 36 people, and class XI IPS 3 totaling 37 people. This study uses a quantitative approach correlational quantitative method. The sampling technique used in this study was systematic sampling technique. Data were collected through a questionnaire instrument consisting of two independent variables and one dependent variable using a Likert scale. To calculate the prerequisite assumption test, namely using the normality and linearity test, while to analyze the data using multiple linear regression techniques. Thus, it can be concluded that there is a significant relationship between character values and peer support with academic adjustments being declared acceptable resulting from the results of the simultaneous test (F Test), which obtained significant results as shown by the number 0.000 0.05.